SYNTHESIS FROM D-GLUCOSE OF 1,5-DIDEOXY-1,5-IMINO-L-FUCITOL, A POTENT ALPHA-L-FUCOSIDASE INHIBITOR - Fleet, G; Shaw, A; Evans, S; Evans, S (1985)
1,5-Dideoxy-1,5-imino-L-fucitol (1), synthesised from methyl α-D-glucopyranoside, is a potent competitive inhibitor of the hydrolysis of p-nitrophenyl α-L-fucopyranoside catalysed by α-L-fucosidase (ex. bovine epididymis) causing 50% inhibition of enzymic activity at 2.5 × 10 -8 M.